PERFORMANCE EVALUATION OF LASTON AC-WC UNIT ASPHALT MIXING PLANT, FOR NATURAL RUBBER RESULTS DAKTALITAS & MARSHALL TEST - Kamaluddin Lubis; Nuril Mahda; Irwan (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Natural latex is the sap produced by rubber plants, often found in Sumatra, rubber is a natural product that has the potential to be used for various kinds of human needs, especially for asphalt mixture substitution needs. Natural latex can improve the quality and quality of the asphalt mixture. The method used in testing the 2018 Bina Marga & ASSTHO methods. The use of natural latex first testing for the manufacture of KAO values (optimum Asphalt content) by making test specimens mixed with asphalt content ranging from 3% and 6%. The optimum asphalt content was obtained and then tested by mixing latex with variations in the composition of the mixture starting at 0%, 3%, and 6%. The collision was carried out with a standard proctor with a collision of 2 x 75 until the test object was declared solid and then tested with a Marshall tool. The test results from determining the optimum asphalt content of 4% there are results of 845 kg, 5% asphalt content of 1015 kg, 6 and 7%, and the stability values obtained are 1015kg and 850 kg respectively. this value still meets the specified standard while the ductility test value obtained >1000 mm also still meets. Meanwhile, at levels of 3 and 6%, the stability value was reduced and did not meet the standard. The results of the tests showed the addition of latex substitution with high latex content, ductility was still met but the stability value decreased on the contrary